Analisis Problematika Penegakan Hukum Terhadap Tindak Pidana Perjudian Online di Indonesia - Sulthanah, Miska Yusri; Ginting, Rehnalemken (Lembaga Pengembangan Kinerja Dosen, 2025)
The rapid development of technology has led to a transformation in gambling practices, shifting from physical establishments to online platforms. However, law enforcement in Indonesia continues to struggle with multiple challenges in addressing this issue. This research aims to assess the enforcement of online gambling laws based on Lawrence M. Friedman’s legal system theory. It focuses on how legal structure, legal culture, and legal substance interact in the enforcement process. The findings demonstrate that, first, in terms of legal substance, existing regulations are not yet fully effective in combating online gambling. Second, from the perspective of legal structure, law enforcement agencies face persistent challenges in combating online gambling. Third, from the perspective of legal culture, public legal awareness remains relatively low.